Engineered bacterial voltage-gated sodium channel platform for cardiac gene therapy - Hung X. Nguyen; Tianyu Wu; Daniel Needs; Hengtao Zhang; Robin M. Perelli; Sophia DeLuca; Rachel Yang; Michael Pan; Andrew P. Landstrom; Craig Henriquez; Nenad Bursac (Nature Communications, 2022)
Abstract Therapies for cardiac arrhythmias could greatly benefit from approaches to enhance electrical excitability and action potential conduction in the heart by stably overexpressing mammalian voltage-gated sodium channels. However, the large size of these channels precludes their incorporation into therapeutic viral vectors. Here, we report a platform utilizing small-size, codon-optimized engineered prokaryotic sodium channels (BacNav) driven by muscle-specific promoters that significantly enhance excitability and conduction in rat and human cardiomyocytes in vitro and adult cardiac tissues from multiple species in silico. We also show that the expression of BacNav significantly reduces occurrence of conduction block and reentrant arrhythmias in fibrotic cardiac cultures. Moreover, functional BacNav channels are stably expressed in healthy mouse hearts six weeks following intravenous injection of self-complementary adeno-associated virus (scAAV) without causing any adverse effects on cardiac electrophysiology. The large diversity of prokaryotic sodium channels and experimental-computational platform reported in this study should facilitate the development and evaluation of BacNav-based gene therapies for cardiac conduction disorders.